Ligand π-radical interaction with f-shell unpaired electrons in phthalocyaninato-lanthanoid single-molecule magnets: a solution NMR spectroscopic and DFT study - Damjanović, Marko; Morita, Takaumi; Katoh, Keiichi; Yamashita, Masahiro; Enders, Markus (Chemistry - a European journal, 2015)
The phthalocyaninato double-decker complexes [M(obPc)2]0 (M= YIII, TbIII, DyIII; obPc=2,3,9,10,16,17,23,24-octabutoxyphthalocyaninato), along with their reduced ([M(obPc)2]−[P(Ph)4]+; M=TbIII, DyIII) and oxidized ([M(obPc)2]+[SbCl6]− (M=YIII, TbIII) counterparts were studied with 1H, 13C and 2D NMR. From the NMR data of the neutral (i.e., with one unpaired electron in the ligands) and anionic TbIII complexes, along with the use of dispersion corrected DFT methods, it was possible to separate the metal-centered and ligand-centered contributions to the hyperfine NMR shift. These contributions to the 1H and 13C hyperfine NMR shifts were further analyzed in terms of pseudocontact and Fermi contact shifts. Furthermore, from a combination of NMR data and DFT calculations, we have determined the spin multiplicity of the neutral complexes [M(obPc)2]0 (M=TbIII and DyIII) at room temperature. From the NMR data of the cationic TbIII complex, for which actually no experimental structure determination is available, we have analyzed the structural changes induced by oxidation from its neutral/anionic species and shown that the interligand distance decreases upon oxidation. The fast electron exchange process between the neutral and anionic TbIII double-decker complexes was also studied.
Gesehen am 18.01.2021